Compounding method of glass fiber sandwiched sponge

By using ceramicized silicone rubber solution in glass fiber-clad sponge composite material for negative pressure impregnation treatment, a multi-layer structure composite material is formed, which solves the shortcomings of existing materials in terms of peel strength and thermal insulation performance, and significantly improves fire resistance and explosion-proof capability.

CN119408291AActive Publication Date: 2025-02-11HUBEI SHIFENG NEW MATERIALS CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411690997.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing fiberglass clip sponge composite materials have shortcomings in peel strength and thermal insulation performance, making it difficult to effectively prevent thermal runaway and fire in lithium-ion batteries.

Method used

The ceramic silicone rubber solution is used for composite, and the ceramic silicone rubber solution is uniformly penetrated into the sponge pores through the negative pressure impregnation structure to form a multi-layered glass fiber-clad sponge composite material to enhance the bonding strength and thermal insulation performance.

Benefits of technology

It improves the peel strength and thermal insulation performance of composite materials, enhances the fire and explosion-proof capabilities, and effectively prevents thermal runaway and fire from lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119408291A_ABST
    Figure CN119408291A_ABST
Patent Text Reader

Abstract

The invention provides a compounding method of glass fiber sandwiched sponge, and belongs to the technical field of composite materials. The preparation method comprises the following steps: compounding a layer of electronic-grade glass fiber cloth and a layer of polyurethane sponge through ceramic silicone rubber liquid to obtain glass fiber sponge composite cloth; compounding the two pieces of glass fiber sponge cloth prepared in the step A by using a ceramic silicone rubber liquid by taking the sponge side as a composite surface to obtain a plurality of glass fiber sponge-sandwiched composite layers of which the outer sides are both electronic-grade glass fiber cloth; gluing operation before compositing between the electronic-grade glass fabric and the polyurethane sponge is completed through a negative-pressure glue dipping structure, the negative-pressure glue dipping composite structure comprises a glue groove located on the lower side of the polyurethane sponge layer and a fan cover located on the upper side of the polyurethane sponge layer, and a plurality of fabric guide rollers are arranged at an opening in the lower portion of the fan cover. A gap is formed between every two adjacent cloth guide rollers, the upper portion of the fan cover is connected with a negative pressure air source, and a plurality of gluing rollers are arranged at an opening in the upper portion of the glue groove and partially located below the liquid level in the glue groove. The adhesive has the advantages of high peel strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a composite method of glass fiber sandwiched with sponge. Background Art

[0002] With the development of the new energy vehicle industry and the energy storage industry, the safety of power batteries and energy storage batteries has become an increasingly important focus of the industry. Due to the inherent chemical activity / instability of lithium-ion batteries, lithium-ion power / energy storage batteries are prone to thermal runaway or even fire / deflagration / explosion accidents during storage and operation due to bumps, punctures, shocks caused by external forces, or because of their inherent chemical instability. When a lithium-ion battery catches fire, the fire spreads extremely rapidly, and the firefighting time left for the energy storage power station is very short, and they can only wait for the fire to burn out; similarly, compared with the spontaneous combustion of fuel vehicles, when new energy vehicles equipped with lithium-ion power batteries spontaneously combust, the time left for passengers to escape is extremely short, which poses great danger to passengers. Therefore, with the development of the new energy vehicle industry and the energy storage industry, solving the resulting thermal runaway fire prevention problem has always been a key issue that needs to be solved.

[0003] In view of the excellent flame retardant and fireproof properties of silicone rubber, as well as its extremely low price and higher strength compared to aerogel materials (which have both excellent thermal insulation and fireproof properties, but extremely low strength and extremely high price), utilizing the excellent fireproof properties of silicone materials and giving them excellent thermal insulation properties to achieve excellent thermal insulation and fireproof properties while being economical is a very possible way to solve the thermal runaway fire prevention problem of lithium-ion batteries.

[0004] On the basis of silicone rubber, ceramic flame retardant is added, and a ceramic layer is formed through its ceramic properties when burned by high-temperature flame. The above ceramic silicone is added to the composite position of sponge and glass fiber for bonding to obtain a glass fiber sandwich sponge composite material with good thermal insulation and flame retardant properties. At present, most of the composite methods adopt the traditional glue coating and rolling method. This method is difficult to adapt to the porous structure of the sponge, so that the ceramic silicone liquid can evenly penetrate into the sponge pores to enhance the bonding strength and improve the thermal insulation performance (ceramic silicone material fills and seals the open-cell pores of the polyurethane sponge layer). Therefore, based on the coating and dipping of the porous and irregular pore structure of the sponge, it is necessary to design a composite method that is adapted to optimize the properties of the composite material. Summary of the invention

[0005] The purpose of the present invention is to provide a composite method of glass fiber sandwiched with sponge in view of the above problems existing in the prior art. The technical problem to be solved by the present invention is how to improve the peel strength and of the composite material.

[0006] The object of the present invention can be achieved by the following technical scheme: a composite method of glass fiber sandwich sponge, characterized in that it includes the following steps: A, firstly compounding a layer of electronic grade glass fiber cloth and a layer of polyurethane sponge by ceramicized silicone rubber liquid to obtain a glass fiber sponge composite cloth; B, compounding the two glass fiber sponge cloths obtained in step A with the sponge side as the composite surface by using ceramicized silicone rubber liquid to obtain a glass fiber sandwich sponge composite multilayer with two outer sides being electronic grade glass fiber cloth; in step A, the gluing operation before the composite between the electronic grade glass fiber cloth and the polyurethane sponge is completed by a negative pressure dipping structure, the negative pressure dipping composite structure includes a glue groove respectively located on the lower side of the polyurethane sponge layer and a wind shield located on the upper side of the polyurethane sponge layer, a plurality of cloth guide rollers are arranged at the lower opening of the wind shield, and there is a gap between adjacent cloth guide rollers, the upper part of the wind shield is contracted to form an exhaust pipe, the exhaust pipe is connected to a negative pressure air source, and a plurality of glue coating rollers are arranged at the upper opening of the glue groove, and the glue coating roller part is located below the liquid level in the glue groove.

[0007] Furthermore, before the polyurethane sponge enters the negative pressure dipping structure, the electronic grade glass fiber cloth and the polyurethane sponge are clamped by two pressure rollers 1, and after the polyurethane sponge leaves the negative pressure dipping structure, the electronic grade glass fiber cloth and the polyurethane sponge are pressed and fitted by two pressure rollers 2.

[0008] Furthermore, the polyurethane sponge is a flame retardant sponge with a high closed porosity and an air permeability of 30L / m 2 / s~150L / m 2 / s.

[0009] Furthermore, the electronic-grade glass fiber cloth and the polyurethane sponge are heat-dried after being compounded, and are naturally cooled after the heat drying is completed.

[0010] Furthermore, after the two layers of glass fiber sponge cloth are coated with glue and compounded, they are naturally cooled by a cloth guide rack and then rolled up.

[0011] This solution utilizes the air permeability of the polyurethane sponge to roll-coat the glue on the composite surface of the sponge multiple times in small amounts. After each roll-coating, the glue can penetrate into the pores of the broken wall bubbles of the sponge under the action of negative pressure. After multiple roll-coatings and glue penetration, the glue forms a bonding layer on the composite surface of the sponge. The bonding layer is formed after the sponge is infiltrated with glue. The glue solidifies and seals the pores to form a ceramic insulation layer. The final product is a seven-layer structure, which includes, from one side to the other, an electronic-grade glass fiber cloth layer, a glue-infiltrated sponge layer, a polyurethane sponge layer, a glue-infiltrated sponge layer, a polyurethane sponge layer, a glue-infiltrated sponge layer and an electronic-grade glass fiber cloth layer. In this composite material, in order to prevent the ceramic silicone rubber from cracking due to slight expansion of the ceramic layer when it is burned by high-temperature flames to form a ceramic layer, thereby damaging the thermal insulation and fire resistance of the ceramic silicone rubber, electronic-grade glass fiber cloth layers are respectively provided on the outside. The infiltration sponge layer formed by the ceramic silicone rubber infiltrating into the sponge pores can block the pores of the pores, making it more resistant to expansion, shape-keeping, and more compact. The negative pressure and roller pressing after compounding can not only make the glue penetrate into the sponge and fill the pores, but also effectively eliminate the bubbles formed during the glue filling process. The thermal insulation performance is enhanced by the presence of multiple infiltration sponge layers and the alternating arrangement of multiple polyurethane sponge layers with low air permeability. The hot air flow is difficult to pass through the polyurethane sponge layer due to the low air permeability. Combined with the thermal insulation and fireproof properties of the ceramic material itself, the temperature resistance, fire resistance, and heat insulation of the entire composite material are improved. The presence of the infiltration sponge layer is conducive to the transition between different materials, and the mechanical properties are enhanced. After the glue penetrates into the sponge, the bonding strength between the sponge and the sponge, and the sponge and the glass fiber cloth can be greatly improved, and the peeling strength is high, which is equivalent to using the sponge to form a rough bonding surface and a grid structure of the glue storage bonding surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a schematic diagram of the composite structure of glass fiber sandwich sponge composite material.

[0013] Figure 2 It is a structural schematic diagram of a negative pressure dipping structure.

[0014] Figure 3 Schematic diagram of the layered structure of the prepared seven-layer composite material.

[0015] In the figure, 1. negative pressure glue dipping structure; 2. glue tank; 3. wind hood; 4. cloth guide roller; 5. glue coating roller; 6. pressure roller one; 7. pressure roller two; a. electronic grade glass fiber cloth layer; b. glue-infiltrated sponge layer; c. polyurethane sponge layer. DETAILED DESCRIPTION

[0016] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0017] Preparation of ceramic silicone rubber compound

[0018] The vinyl polysiloxane with a viscosity of 10000mPa·S / 25℃ (VS10000 produced by Anbiya Special Silicone (Nantong) Co., Ltd.) and the base glue with a viscosity of 750000mPa·S / 25℃ (6345 base glue produced by Dongguan Chuanshi Electronic Technology Co., Ltd.) in component A were weighed in a ratio of 3:7. The flame retardant (CFR-2 flame retardant produced by Anhui Yishitong Material Technology Co., Ltd.) was weighed in a ratio of 1.2:1 to the sum of the flame retardant and the vinyl polysiloxane and the base glue. Flammable agent), a cross-linking agent with a hydrogen content of 16 mmol / g (side chain hydrogen-containing silicone oil H=1.6 from Jiande Polymer New Materials Co., Ltd.) was weighed according to the addition ratio of the cross-linking agent to the sum of vinyl polysiloxane and base gum of 0.0054:1, and a catalyst (PT-5000 from Zhongshan Zijun Chemical) and an inhibitor (OS121 from Shenzhen Ousbang New Materials Co., Ltd.) were weighed according to the addition ratio of the catalyst and the inhibitor to the sum of vinyl polysiloxane and base gum of 0.005:1. The vinyl polysiloxane with a viscosity of 10000mPa·S / 25℃ (VS10000 from Anbia Special Silicone (Nantong) Co., Ltd.) and the base glue with a viscosity of 750000mPa·S / 25℃ (6345 base glue from Dongguan Chuanshi Electronic Technology Co., Ltd.) in component B were weighed in a ratio of 3:7, the flame retardant (CFR-2 flame retardant from Anhui Yishitong Materials Technology Co., Ltd.) was weighed in a ratio of 1.2:1 between the flame retardant and the sum of the vinyl polysiloxane and the base glue, and the cross-linking agent with a hydrogen content of 16mmol / g (side chain hydrogenated silicone oil H=1.6 from Jiande City Polymer New Materials Co., Ltd.) was weighed in a ratio of 0.0054:1 between the cross-linking agent and the sum of the vinyl polysiloxane and the base glue. Then, the A and B components were stirred respectively by a double planetary mixer at a twist pulp speed of 100RPM and a double-layer dispersion disk speed of 3000RPM, and vacuumed to -100KPa while stirring. The mixture was cooled by a circulating water cooler simultaneously, and the material temperature of the A and B components was controlled to be below 20°C. The mixture was stirred for 20 minutes to obtain the A and B components of the ceramic silicone rubber compound.

[0019] Preparation of glass fiber sandwich sponge composite thermal insulation and fireproof material

[0020] Mix the prepared ceramic silicone rubber compound A and B components evenly and then continuously and quantitatively inject them into the rubber tank. Figure 1 and Figure 2As shown, after the electronic-grade glass fiber cloth and the 2.2mm thick KZ314FM-70PPI polyurethane sponge produced by our company are clamped by the pressure roller 6, the electronic-grade glass fiber cloth is separated from the sponge to avoid the glue groove 2, and the sponge passes through the position between the glue groove 2 and the wind hood 3, and is supported and guided by the cloth guide roller 4 and the glue coating roller 5, and the negative pressure in the wind hood 3 is controlled to be about 50Mpa. By continuously applying glue to the sponge and negative pressure infiltration, the glue can penetrate into the sponge with a certain thickness and the cloth penetrates the sponge layer with a high closed-pore rate. After the infiltration is completed, the pressure roller 7 clamps the sponge and the glass fiber cloth to flatten them, and then puts them into a blast drying oven and heats and cures them at 110-130°C for 5 minutes to obtain a semi-finished product of a double-layer composite of glass fiber sponge. The two semi-finished products that have been naturally cooled are further mixed with the A and B components of the ceramic silicone rubber compound and coated on the smooth surface of the polyurethane sponge, and then rolled flat by a double-roll calender, placed in a blast drying oven and heated and cured at 110-130°C for 5 minutes to obtain a finished product with a thickness of 5 mm. The final product is a Figure 3 The seven-layer structure shown, from one side to the other, is electronic-grade glass fiber cloth layer a, glue-infiltrated sponge layer b, polyurethane sponge layer c, glue-infiltrated sponge layer b, polyurethane sponge layer c, glue-infiltrated sponge layer b and electronic-grade glass fiber cloth layer a.

[0021] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A composite method of glass fiber sandwiched with sponge, characterized in that: The invention comprises the following steps: A. firstly compounding a layer of electronic-grade glass fiber cloth and a layer of polyurethane sponge by means of ceramicized silicone rubber liquid to obtain a glass fiber sponge composite cloth; B. compounding the two glass fiber sponge cloths obtained in step A by means of ceramicized silicone rubber liquid with the sponge side as the compounding surface to obtain a glass fiber sponge composite multilayer with both outer sides being electronic-grade glass fiber cloth; in step A, the gluing operation before compounding between the electronic-grade glass fiber cloth and the polyurethane sponge is completed by means of a negative pressure gluing structure (1), the negative pressure gluing composite structure comprising a glue groove (2) respectively located at the lower side of the polyurethane sponge layer and a wind shield (3) located at the upper side of the polyurethane sponge layer, a plurality of cloth guide rollers (4) being arranged at the lower opening of the wind shield (3), a gap being provided between adjacent cloth guide rollers (4), the upper part of the wind shield (3) being contracted to form an exhaust pipe, the exhaust pipe being connected to a negative pressure air source, a plurality of gluing rollers (5) being arranged at the upper opening of the glue groove (2), the gluing rollers (5) being partially located below the liquid level in the glue groove (2).

2. A composite method of glass fiber sandwiched with sponge according to claim 1, characterized in that: Before the polyurethane sponge enters the negative pressure dipping structure (1), the electronic grade glass fiber cloth and the polyurethane sponge are clamped by two pressure rollers (6); after the polyurethane sponge leaves the negative pressure dipping structure (1), the electronic grade glass fiber cloth and the polyurethane sponge are pressed and bonded by two pressure rollers (7).

3. A composite method of glass fiber sandwiched with sponge according to claim 1, characterized in that: Polyurethane sponge is a flame retardant sponge with high closed porosity and air permeability of 30L / m 2 / s~150L / m 2 / s.

4. A composite method of glass fiber sandwiched with sponge according to claim 1, characterized in that: The electronic grade glass fiber cloth and the polyurethane sponge are heat dried after compounding, and then naturally cooled after heat drying.

5. A composite method of glass fiber sandwiched with sponge according to claim 1, characterized in that: After the two layers of glass fiber sponge cloth are coated with glue and compounded, they are naturally cooled by the cloth guide rack and then rolled up.

Citation Information

Patent Citations

  • Composite construction's polyurethane environmental protection sponge

    CN204894702U

  • Composite floor mat

    CN207059408U

  • Automobile door panel interior trim

    CN213704825U

  • Composite panel

    GB1395435A

  • Thickening-assisting pad and method for producing the same

    JP2003253511A